Genome sequence of an unclassified pleosporales species isolated from human nasopharyngeal aspirate - Ng, K.P.; Yew, S.M.; Chan, C.L.; Soo-Hoo, T.S.; Na, S.L.; Hassan, H.; Ngeow, Y.F.; Hoh, C.C.; Lee, K.W.; Yee, W.Y. (2012)
Pleosporales is the largest order in the fungal class Dothideomycetes. We report the 36,814,818-bp draft genome sequence and gene annotation of UM1110, a Pleosporales isolate associated with unclassified genera that is potentially a new fungal species. Analysis of the genome sequence led to the finding of genes associated with fungal adhesive proteins, secreted proteases, allergens, and pseudohyphal development.